Titanocene thiolates [Ti]Cl(SCHR-2-cC4H3S) and [Ti](SCHR-2-cC4H3S)2 (R = H, Me): Synthesis, properties and reaction chemistry. (1st July 2018) - Taher, Deeb; Klaib, Sami; Stein, Thomas; Korb, Marcus; Rheinwald, Gerd; Ghazzy, Asma; Lang, Heinrich
Graphical abstract: Synthetic methodologies for the preparation of the [Ti]Cl(SCHR-2- c C4 H3 S) and [Ti](SCHR-2- c C4 H3 S)2 complexes are discussed. Their reaction behavior towards Pd and Pt halides is reported, whereby sulfur–halide exchange reactions occurred. The hydrolysis reaction of [Ti](SCHR c C4 H3 S)2 gave the titanoxane cluster [(Ti(η 5 -C5 H4 SiMe3 ))6 O9 ], the structure of which in the solid state was determined by single X-ray structure analysis. Abstract: Titanocene dichloride, [Ti]Cl2 (1 ) ([Ti] = Ti(η 5 -C5 H4 SiMe3 )2 ), with one equiv. of the lithium thiolates LiSCHR-2- c C4 H3 S (2a, R = H; 2b, R = Me) gave the appropriate [Ti](Cl)(SCHR-2- c C4 H3 S) compounds (3a, R = H; 3b, R = Me) under mild reaction conditions. Further treatment of 3a, b with another equiv. of thiolates 2a, b produced the respective bis(thiolates) species [Ti](SCHR-2- c C4 H3 S)2 (4a, b ). Titanocenes 4a, b are also accessible, when 1 is reacted with 2a, b in a 1:2 M ratio. The hydrolysis reaction of 4a, b produced the titanoxane cluster 5, consisting of a [Ti′]6 O9 cage ([Ti′] = Ti(η 5 -C5 H4 SiMe3 )) with a silsesquioxane analog structure. The molecular structure of 5 in the solid state is the first example of a trigonal prismatic Ti6 -polyhedron. Upon treatment of 4a, b with MCl2 (M = Pd, Pt), aiming to obtain heterobimetallic coordination complexes, however, either 1 or 3a, b were formed, depending on the reaction conditions. All the compounds have been characterized by elemental analysis, IR, NMR ( 1 H, 13 C{ 1 H}) spectroscopy and mass-spectrometry.